THE ROLE OF THE VILLAGE HEAD IN PREVENTING CORRUPTION CRIMES WITH THE ALLOCATION OF VILLAGE FUNDS: PERAN KEPALA DESA DALAM PENCEGAHAN TINDAK PIDANA KORUPSI DENGAN ALOKASI DANA DESA - Libertina Waruwu, Nini (UPMI Proceeding Series, 2024)
Overall village financial management activities which include planning, implementation, administration, reporting and accountability of village finances. The financial management referred to is the management of the Village Revenue and Expenditure Budget (APBDes) to support and carry out planned village government work programs. The research method in writing this thesis is the empirical research method. The empirical research referred to is research whose object of study includes basic norms or rules, legal principles, statutory regulations, comparative law, doctrine and jurisprudence. Regulation of the role of village heads in preventing corruption with the allocation of village funds by issuing PMK No. 201/PMK.07/2022 concerning Village Fund Management. Deli Serdang Regent Regulation Number 17 of 2022 concerning the second amendment to Deli Serdang Regent Regulation Number 03 of 2019 concerning Village Financial Management. The village head's obstacles in preventing corruption by allocating village funds for the realization of preventing corruption are first, low understanding of the anti-corruption movement in the form of fulfilling monitoring and evaluation elements, fulfilling documents during planning and implementation and administration of activities. Second, a form of preventing corruption is by feeling afraid of violating the regulations implementing the use of village funds. Third, the discussion regarding prevention of corruption seems to be a new study and is taboo for further discussion. Implementation of the village head's role in preventing corruption by allocating village funds. The Village Head in Village Fund Management in Tanjung Morawa B Village includes planning, implementation, administration, reporting and accountability. In managing village finances, the principles of accountability, transparency and participation have been implemented where strategic plans are implemented through the Musrenbangdes forum (Village Development Planning Conference).